Pembangunan Dan Keberkesanan Aplikasi Mobil Permainan Pendidikan Bagi Murid Masalah Pembelajaran Dalam Mempelajari Pecahan - Supermaniam, Murugesu (2023)
Fraction is one of the topics covered in the secondary school mathematics syllabus in Malaysia. This difficulty is more felt by learning problem students who have a shortage compared to typical students. Therefore, this study is conducted to develop and test the effectiveness of learning strategies through the Mobile Game Education app for the KSSMPK fractional syllabus (P-KSSMPK) with its self-explanation (P-KSSMPKps) and low-level technology such as QR-link instruments fraction and YouTube, Mountingboard Graphic pictures, textbooks, and whiteboards. It involves 152 special education students with Form 1, 2 and 3 students who follow the Secondary School Standards of Special Education Secondary School (KSSMPK) from 10 secondary schools with special education integration programs in districts North Kinta, Perak. This research was conducted to ensure that the learning mode method was supported by the component composition and efficient mobile application modes to improve the achievement and interest among students in particular. This study is conducted based on the design of quasi-experimental studies with Factorial 3 x 2, considering different levels of ability (high/low) per respondent. The dependent variable is the achievement and interest of students in the use of mobile applications in fraction education, independent variables are Mobile Application Mode Education, and moderator variables are the level of student capabilities.